Pembelajaran Kolaboratif Sebagai Strategi Membentuk Karakter Disiplin Siswa (Studi Kasus di SMA Negeri 2 Tambun Utara Bekasi) - Amiruddin, Nurannisa Rahmadani; Lubis, Adlan Fauzi (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the strategies implemented by Islamic Religious Education teachers in fostering students’ academic discipline character through collaborative learning at SMA Negeri 2 Tambun Utara. The research employs a qualitative approach using a case study design. Data collection techniques include observation, interviews, and documentation. The findings reveal that collaborative learning is carefully designed by incorporating academic discipline values into learning objectives, classroom regulations, group task allocation, and time management. The implementation takes place through structured group activities, well-defined roles, and continuous guidance from the teacher. Through this approach, students develop disciplined behaviors such as being punctual, complying with rules, actively engaging in discussions, and assuming responsibility for both individual and group tasks. Furthermore, students’ academic discipline character shows improvement, as reflected in greater awareness of punctuality, preparedness for learning, and academic responsibility. Thus, collaborative learning is considered effective in enhancing students’ academic discipline character. Keywords: Academic Discipline Character, Collaborative Learning, Learning Strategy, High School Students